Frequency of Non-Alcoholic Fatty Liver Disease in Non-obese Type 2 Diabetic Patients and its Association with Sex and Age - Umair, Muhammad; Malik, Muhammad Omar; Habib, Syed Hamid; Shah, Mohsin; Ullah, Atif (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Objective: This study aims to explore the frequency of non-alcoholic fatty liver disease (NAFLD) in non-obese Type 2 Diabetes Mellitus (T2DM) patients and its association with diabetic control in different age and sex groups. Study Design: Cross sectional observational study. Place and Duration of Study: The study was conducted at outpatient department of District Headquarter Hospital Dera Ismail Khan, Pakistan from a period of March 2016 to August 2016. Materials and Methods: This study involved 100 already diagnosed T2DM patients with BMI ranging from 18.5 to 29.9. 55% were male and 45% were female. Age limit was 30-60 years. Mean age of the patients was 46.78 ± 8.39 years. Diagnosis of NAFLD was performed by ultrasonography. Results: The results showed fifty eight (58%) of these patients had fatty liver. NAFLD had no significant association with different age (< 45 years and ≥ 45 years, p=0.847) and sex groups (p = 0.392), although males were found to have higher prevalence than females (61.8 % vs. 53.3 %). Conclusion: NAFLD is a highly prevalent disorder in non-obese T2DM patients and was found to have no significant association with different age and sex groups